The Generalizability of Police Legitimacy: Procedural Justice, Legitimacy, and Speeding Intention of South Korean Drivers - Kim, Yeon Soo (Asian journal of criminology, 2019)
Empirical support for procedural justice theory in criminology is robust in the developed Western countries, whereas the results are mixed for non-Western or less-developed countries. Some scholars (e.g., Reisig et al. Journal of Criminal Justice and Security, 14(2), 147-164, 2012) argue that the generalizability of procedural justice theory may be limited to particular sociological settings, such as democratic and industrialized societies. The current study aims to review the international generalizability of the theory and to test the theory utilizing a South Korean driver sample. The results show that procedural fairness predicted legitimacy and speeding intention. However, perceived legitimacy does not mediate the association between perceived procedural fairness and speeding intention for Korean drivers. Considering the findings from the current study and previous studies, it seems that industrialization may not be a sufficient condition linking perceived legitimacy and compliance, but democracy may be the most significant precursor for the theory to work.